SMALL-MEDIUM ENTERPRISE DEVELOPMENT AND FINANCING ISSUES - Д.Сувдаа; Ё.Чимэдцогзол (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Small and medium-sized enterprises /SMEs/ and micro businesses play a crucial role in supporting economic growth, providing jobs for the growing population and reducing poverty around the world as well as in Mongolia (UNDP, 1999; World Bank, 2012) In particular, international development organizations, research institutes and governments have highlighted since the 2009 global financial crisis. However, due to economic capacity and financial market conditions in developing countries, the financing of SME’s issue is not improving well. Same as in Mongolia, there are insufficient financing instruments with long term and relatively low interest rates that meet SMEs needs. It is necessary to undertake specific research in this area, to make it more systematic, integrated policy and innovative financing tools. The study examined the international experience of SME finance, while analysed the Mongolian SME financing, its challenges, problems and proposed specific proposals and recommendations.